Analysis of Crop Pattern Plant and Irrigation Water Needs in Pauh Tinggi Irigation Network Planning, Pauh Tinggi Village, Kerinci District, Jambi - Acep Hidayat; Muhammad Al Reza Hidayatullah (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2020)
Pauh Tinggi irrigation network planning which has an area of irrigation land of 473 ha. This irrigation plan draws water from the Pauh Tinggi Dam located in the Batanghari Hulu river, Kerinci Regency, Jambi. Population growth which is directly proportional to the increasing necessities of life, one of which is in the food sector, has made the government take the initiative to meet the needs and welfare of the community by opening land into productive areas of rice fields and fields, and making irrigation plans. In making irrigation planning, hydrological and rainfall calculations are needed to be able to make the right cropping system for farmers in Pauh Tinggi Village, Kerinci Regency, Jambi. A calculation of 17 alternative cropping patterns with different types of plant variants and different plans for the initial planting period were carried out by comparing with the mainstay debit factor (Q80). It was found that the cropping pattern is very possible always using the RICE-RICE-CROP cropping pattern. The most efficient and optimal planting pattern is the alternative planting pattern 14 in the form of RICE -RICE-CORN with Netto Field Water Requirements in tertiary plots (NFR tertiary) ranging from 0 - 1.30 ltr / sec / ha with a maximum of 1.30 ltr / sec / ha in January I, while irrigation water needs in the intake (DR intake) range 0 - 1.60 ltr sec / ha with a maximum of 1.60 ltr / sec / ha in January I.